The Illusion of International Development: Authoritarian Infrastructuralism and Spin Dictatorship in the Laos-China Railway - Honest Dody Molasy (International Journal Labs, 2026)
Large-scale market integration and infrastructure development have long been regarded as accelerators of political liberalization in the Global South, according to conventional modernization theory. A significant exception to this assumption, however, is the operationalization of the Laos–China Railway (LCR). This massive undertaking has ironically reinforced the authoritarian tenacity of the Lao People’s Revolutionary Party (LPRP) rather than promoting democratic liberalization. This article argues that the LCR serves more as a tool for political survival than as a means of transportation, drawing on Spin Dictatorship theory. The regime uses the project to construct a concept of Performative Modernity—an impressive display of technological prowess designed to project performance credibility while concealing systemic oppression and financial instability. The analysis demonstrates how the LPRP manipulates the narrative of “transforming from land-locked to land-linked” to justify exclusionary development through a qualitative case study employing process tracing. By introducing the concept of Authoritarian Infrastructuralism and challenging the liberal institutionalist perspective, this study shows that infrastructural connectivity can be effectively decoupled from democratic transformation, thereby supporting the consolidation of contemporary autocracy.